EDUCATIONAL LEADERSHIP IN ISLAM REFERRING TO AN INTERDISCIPLINER PERSPECTIVE - Asdlori Asdlori; Yulian Purnama (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Technological progress will have an impact on social changes in society. Along with these advances, the challenges of leadership have also changed in the face of these technological changes. This study tries to examine various literature related to leadership, politics and technological challenges in an effort to find the problems of the study to be discussed. Then the findings were as follows; First, leadership from a sociological perspective is leadership that faces challenges in accordance with technological developments. To deal with it, then as a leader it is necessary to implement the AGIL system by holding Islamic principles. Second, leadership from a political perspective is a leader who has challenges with individuals, institutions, organizations, parties and other institutions so that in facing these challenges.